Community, vulnerability and reproduction in disaster conditions. Approaches from Latin America and the CaribbeanIntroduction to dossier - Ana Gabriela Fernández; Johannes Waldmüller; Cristina Vega (Íconos)
The following introductory article addresses the vulnerability approach towards disasters in the social sciences from different Latin American contemporary perspectives. First of all, the elements that propose a vision about vulnerability and its initial approaches are presented and put into critical dialogue with the resilience approach. Concerns are raised when the resilience of the affected population is emphasized as a mechanism of participa-tion in recovery. Secondly, the contributions of gender studies and the reproduction of life in disaster contexts are addressed. With the advances and documented experiences in the area of gender and disasters considered, a connection between vulnerability and the reproduction and care approach is established with the objective of shedding light on possible alternative routes in the production of knowledge and its influence over policies. Finally, themes for debate and reflection are proposed, attempting to contribute to a discussion that is currently in tension in the academia and in the implementation of public policies or actions executed by international cooperation organisms.